DEVELOPING THE STUDENTS’ ABILITY IN READING THROUGH SPEED READING TECHNIQUE - La Ode Muh. Idrus Hamid B.; Muhammad Yunus (Universitas Sembilanbelas November Kolaka, 2016)
This study was designed to improve the Students’ Ability in Reading through Speed Reading at the first year of SMKN 1 Watunohu. The writer formulated a study question “How can speed reading developing the students’ ability in reading at the second year of first year of SMKN 1 Watunohu?” In addition, the objective of the study was generally aimed to improve the students’ reading ability through speed reading at the first year of SMKN 1 Watunohu.The design of this study was collaborative Classroom Action Research (CAR). It means that when doing the study, the writer collaborated with the English teacher of first year of SMKN 1 Watunohu. The subject of this study was the first year of SMKN 1 Watunohu in academic year of 2014/2015. This study was conducted in two cycles.The development of students’ ability in reading at the first year of SMKN1 Watunohu supported by some evidences. First, it could be seen from the improvement of the average students’ value which showed from preliminary study the students only reached average 43.56 or only 32% or 6 from 26 students got the score greater than or equal to 72. Second, the average of the students’ value was58.74 in the first cycle where only 44% or 8 from 26 students got the score greater than or equal to 72.Meanwhile in the second cycle, the average value of the students’ reading ability through speed reading became 87.42, there were 88.00% or 24 from 26 students got the greater than or equal to 72. Third, the students were actively involved in the teaching and learning process. It can be seen from the result of analysis of observation sheet. So it can be concluded that speed reading can improve the students’ reading ability at the first year of SMKN 1 Watunohu